2004
DOI: 10.1103/physreve.70.036103
|View full text |Cite
|
Sign up to set email alerts
|

Emergent oscillations in unidirectionally coupled overdamped bistable systems

Abstract: It is well known that overdamped unforced dynamical systems do not oscillate. However, well-designed coupling schemes, together with the appropriate choice of initial conditions, can induce oscillations when a control parameter exceeds a threshold value. In a recent publication [Phys. Rev. E 68, 045102 (2003)]], we demonstrated this behavior in a specific prototype system, a soft-potential mean-field description of the dynamics in a hysteretic "single-domain" ferromagnetic sample. The previous analysis of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 6 publications
2
36
1
Order By: Relevance
“…A recent example is the study of UPOs in relation to the emergence of chaotic behavior in rings of Duffing oscillators. 7 Closest to the dynamics of the gene system studied here are the rings of unidirectionally coupled magnetic cores 9 that have been not only studied numerically but also implemented experimentally by Bulsara et al In the antiferromagnetic case, the system of coupled magnetic cores is described by the following ODEs (Ref . 9):…”
Section: Comparison To Other Unidirectionally Coupled Rings: Fluxmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent example is the study of UPOs in relation to the emergence of chaotic behavior in rings of Duffing oscillators. 7 Closest to the dynamics of the gene system studied here are the rings of unidirectionally coupled magnetic cores 9 that have been not only studied numerically but also implemented experimentally by Bulsara et al In the antiferromagnetic case, the system of coupled magnetic cores is described by the following ODEs (Ref . 9):…”
Section: Comparison To Other Unidirectionally Coupled Rings: Fluxmentioning
confidence: 99%
“…Loops or ring structures of nonlinear elements [5][6][7] constitute one of the simplest topologies of practical interest in biology and engineering. [8][9][10][11] For instance, in a recent series of papers, 3,9,12,13 Bulsara et al reported the implementation through electronics of rings of unidirectionally coupled magnetic flux gates and their successful experimental use as a highly sensitive magnetic field sensors. The mathematical analysis of the steady-state dynamics of a variety of such ring systems has also revealed the richness of their dynamical attractors, including multistability, unstable periodic solutions, quasiperiodicity and even chaos and hyperchaos.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This network symmetry is critical in the creation of a heteroclinic cycle and, more importantly, in the accompanying infinite-period bifurcations of limit cycle oscillations. Indeed, a bifurcation analysis [3,6] reveals that the system (4) displays oscillatory behavior with the following features:…”
Section: Network Architecturementioning
confidence: 99%
“…The oscillations emerge through a global branch of heteroclinic connections between steady states, so that near the onset of the cycle, the accompanying oscillations exhibit long periods, which in turn renders their waveform highly sensitive to symmetry-breaking effects caused by very small external signals. This critical observation has led to the fabrication of highly-sensitive sensors, magnetic-and electric-field ones, whose operation relies mainly on the coupling signal that travels from one bistable system to the next one [3][4][5][6]. That is, in the absence of coupling, each bistable unit cannot oscillate.…”
Section: Introductionmentioning
confidence: 99%